2005
DOI: 10.1002/chem.200401210
|View full text |Cite
|
Sign up to set email alerts
|

A Study of [Co2(alkyne)(binap)(CO)4] Complexes (BINAP=(1,1′‐Binaphthalene)‐2,2′‐diylbis(diphenylphosphine))

Abstract: Understanding the interaction of chiral ligands, alkynes, and alkenes with cobaltcarbonyl sources is critical to learning more about the mechanism of the catalytic, asymmetric Pauson-Khand reaction. We have successfully characterized complexes of the type [Co2(alkyne)(binap)(CO)4] (BINAP=(1,1'-binaphthalene)-2,2'-diylbis(diphenylphosphine)) and shown that diastereomer interconversion occurs under Pauson-Khand reaction conditions when alkyne=HC[triple bond]CCO2Me. Attempts to isolate [Co2(alkyne)(binap)(CO)x] c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 47 publications
4
15
0
Order By: Relevance
“…A resonance corresponding to binap at δ −14.6 ppm was also observed. The 31 P NMR spectrum of 4 was consistent with the 31 P NMR data obtained for diastereoisomers 2 a and 2 b , the structures of which had been confirmed by X‐ray crystallography;10 this, together with the X‐ray characterisation obtained for complex 6 (see below), provided the necessary assurance that complex 4 was the desired binap cobalt derivative of enyne 3 . The two diastereoisomers of 3 , formed in a 2:1 ratio, could not be separated by chromatography or recrystallisation.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…A resonance corresponding to binap at δ −14.6 ppm was also observed. The 31 P NMR spectrum of 4 was consistent with the 31 P NMR data obtained for diastereoisomers 2 a and 2 b , the structures of which had been confirmed by X‐ray crystallography;10 this, together with the X‐ray characterisation obtained for complex 6 (see below), provided the necessary assurance that complex 4 was the desired binap cobalt derivative of enyne 3 . The two diastereoisomers of 3 , formed in a 2:1 ratio, could not be separated by chromatography or recrystallisation.…”
Section: Resultssupporting
confidence: 78%
“…Given that alkyne coordination is the accepted first event in the PKR, we subsequently examined the reactivity of 1 towards alkynes. We found that complex 1 reacted with a range of alkynes to form mixtures of two diastereoisomeric complexes as exemplified by 2 a and 2 b (Scheme ; structures confirmed by X‐ray crystallography) 10. In the case of 2 , the two isomers were separable and 31 P NMR studies revealed that they interconverted without decomposition at 75 °C 10…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Asymmetric cobalt-catalyzed intermolecular Pauson-Khand reactions were reported [997]. An asymmetric intermolecular Pauson-Khand reaction of cobalt-alkyne complexes having a chiral bridging ligand [998] and a rhodium-catalyzed asymmetric Pauson-Khand reaction in water [999] was described.…”
Section: Carbonylations Of Alkynes (Including the Pauson-khand Reaction)mentioning
confidence: 98%
“…While our abovementioned basal anti-bridged BINAP cobalt-alkyne complex was obtained by mixing the cobalt-alkyne complex with (R)-BINAP, 65 Gibson first prepared a precatalyst from either Co 2 (CO) 8 or Co 4 (CO) 12 and (R)-BINAP and then added the alkyne 68 in order to get the chelated complex. Thus, the order of addition seems to play an important role.…”
Section: Scheme 44mentioning
confidence: 99%